#### Question

Solve the following systems of equations:

7(y + 3) − 2(x + 2) = 14

4(y − 2) + 3(x − 3) = 2

#### Solution

The given equations are:

7(y + 3) − 2(x + 2) = 14.............(i)

7y - 2x = -3

4(y − 2) + 3(x − 3) = 2

4y + 3x = 19

Multiply equation (i) by and equation (ii) by and add both equations we get

21y - 6x = -9

8y + 6x = 38

_______________

29y = 29

y = 1

Put the value of x in equation (i)we get

7 x 1 - 2x = -3

=> -2x = -10

=> x = 5

Hence the value of x = 6 and y = 1

Is there an error in this question or solution?

#### APPEARS IN

Solution Solve the Following Systems of Equations: 7(Y + 3) − 2(X + 2) = 14 4(Y − 2) + 3(X − 3) = 2 Concept: Algebraic Methods of Solving a Pair of Linear Equations - Substitution Method.